Editorial - Bernardo-Filho, Mario (Brazilian Journal of Health and Biomedical Sciences, 2019)
Dear All The broad approach of the Brazilian Journal of Health and Biomedical Sciences shows itself again in this issue. The papers are related to a variety of subjects covering different populations. The current issue contains a diversity of interesting and important studies that use practical and convenient techniques involving both young and elderly groups. This stimulates the reader to be in contact with a range of possible information in the health and biomedical sciences area that is highly relevant and current worldwide. In addition, several conditions related to diseases, such as type 2 diabetes mellitus (T2DM), chronic obstructive pulmonary disease (COPD), knee osteoarthritis (KOA), and frailty are presented in the studies. Findings are presented from the clinical evaluation of induced sputum and pulmonary function in patients with T2DM, racial/ethnic differences in bone mineral density, muscle function and fat mass in young women, land-based versus water-based walking programs in elderly women with KOA, processing speed during attention and memory tasks as an indicator of frailty, use of the 6-minute walking test to evaluate patients with respiratory disease, as well as an evaluation of the prevalence of sickle cell trait in blood donors through a systematic review. An epidemiological analysis of exogenous poisoning is also presented. The objectives of the papers published in this issue include: (i) systematizing data related to the prevalence of sickle cell trait among blood donors; (ii) determination of racial/ethnic differences in bone mineral density, muscle function and fat mass in women of Caucasian, East-Asian, South-Asian, Hispanic and African-American backgrounds; (iii) investigation of effects of a walking program with a controlled progressive workload in water compared to land with regard to pain, functional and physical performance, and quality of life in elderly women with KOA; (iv) characterization of the processing speed during attention and memory tasks in a geriatric population in different states of frailty in order to verify the factors that most contribute to the frailty phenotype; (v) comparative cross-sectional study of the 6-minute walking test data with inclusion of individuals with systemic sclerosis, idiopathic pulmonary fibrosis and COPD; (vi) evaluation of cellularity, albumin and interleukin-1 levels in induced sputum to determine respiratory function parameters in patients with T2DM; and (vii) observation of patterns in cases of exogenous poisoning in a region of the State of Minas Gerais, Brazil. Readers of the BJHBS may expect to access relevant discussions of subjects in Health and Biomedical Sciences.